Regulating polysulfide intermediates by ultrathin Co-Bi nanosheet electrocatalyst in lithium−sulfur batteries. (October 2021) - Li, Chuanchuan; Qi, Siyun; Zhu, Lin; Zhao, Ya; Huang, Renzhi; He, Yanyan; Ge, Weini; Liu, Xiaobiao; Zhao, Mingwen; Xu, Liqiang; Qian, Yitai
Highlights: Ultrathin Co-Bi nanosheets intimately grown on reduced graphene oxides composite was conveniently fabricated. The obtained composite has effective performance for regulating polysulfides for the first time. Outstanding cycling stability and a high sulfur mass loading of 9.5 mg cm −2 was achieved. The strong binding strength and electrocatalysis effect of the composite is confirmed by DFT calculations. Graphical Abstract: Co-Bi /rGO composite has been reported for the first time to regulate the polysulfide intermediates, which delivers a high capacity of 1334 mAh g −1 at 0.2 C, impressive rate performance up to 8 C, outstanding cycling stability over 500 cycles at 1 C, and remarkable areal capacity of 8.3 mAh cm −2 with a high sulfur mass loading of 9.5 mg cm −2 . ga1 Abstract: The practical application of lithium–sulfur (Li–S) batteries is hindered by the nonconductivity of sulfur, sluggish reaction kinetics and polysulfide shuttling. The liquid lithium polysulfide intermediates, connecting the Li–S battery electrochemical reaction of sulfur to Li2 S, play a decisive role on battery performance. Herein, Co-Bi nanosheets intimately grown on reduced graphene oxides (Co-Bi /rGO) composite has been reported for the first time to regulate the polysulfide intermediates. The Co-Bi could not only chemically trap polysulfides but also propel the acceleration of polysulfide conversion enabled by a lower free energy and decomposition energy barrier in Li–S reaction process. Therefore, the Co-Bi /rGO–S cathode delivers a high capacity of 1334 mAh g –1 at 0.2 C, impressive rate performance up to 8 C, outstanding cycling stability over 500 cycles at 1 C, and remarkable areal capacity of 8.3 mAh cm –2 with a high sulfur mass loading of 9.5 mg cm –2 . The chemical binding strength, the Gibbs free energy and the energy barrier for transition state from theoretical calculations give a deep insight of polysulfide regulation by Co-Bi .